THE EFFECT OF PERCEIVED USEFULNESS, PERCEIVED EASE OF USE, AND SOCIAL INFLUENCE TOWARD INTENTION TO USE MEDIATED BY TRUST - Kurniawan, Ilham Agung; Mugiono, Mugiono; Wijayanti, Risna (Jurnal Aplikasi Manajemen, 2022)
This research analyses the effect between perceived usefulness, perceived ease of use, social influence, trust, and intention to use on a digital zakat application at Malang City. The object of this research utilizes people who are 23 years of age and over. Besides, they are required to have income, know about a digital zakat application, and are required to pay zakat using the application. This research used a nonprobability sampling method with a purposive sampling technique of 104 respondents. It also utilized smartPLS 3.0 as data analysis. The research instruments involve the inner model test, outer model, conversion path diagram, and hypothesis testing. The result of the analysis reveals perceived usefulness, perceived ease of use, social influence, and trust explicitly affect intention to use the digital zakat application. Trust can mediate the influence of perceived usefulness, perceived ease of use, and social influence toward intention to use. Social Influence and Trust have a dominant influence on intention to use. In this case, service facility providers can promote digital zakat applications through any media to reach potential consumers. It can help them give some recommendations about the use of zakat applications. Moreover, it will help create trust in consumers about using digital zakat applications.